Web Information Systems and Mining International Conference, WISM 2011, Taiyuan, China, September 24-25, 2011, Proceedings, Part I - Gong, Zhiguo; Luo, Xiangfeng; Chen, Junjie; Lei, Jingsheng; Wang, Fu Lee.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The two-volume set LNCS 6987 and LNCS 6988 constitutes the refereed proceedings of the International Conference on Web Information Systems and Mining, WISM 2011, held in Taiyuan, China, in September 2011. The 112 revised full papers presented were carefully reviewed and selected from 472 submissions. The first volume includes 56 papers organized in the following topical sections: applications on Web information systems; applications of Web mining; distributed systems; e-government and e-commerce; geographic information systems; information security; and intelligent networked systems.
Keywords: Computer science; Software engineering; Database management; Data mining; Information storage and retrieval systems; Multimedia systems; Computer Science; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Software Engineering; Data Mining and Knowledge Discovery; Multimedia Information Systems